Flashcard Media as a Game Tool to Improve Early Childhood Cognitive Abilities - Leni Evi Matondang; Tri Hastuti; Yuliastanti Rahayu KW; Siti Mustaghfiroh; Lilis Hidayanti (Universitas Negeri Makassar, 2022)
Improving children's cognitive abilities using flashcard media by playing is the goal to be achieved in this study. This research is a type of experimental research that uses a quantitative approach. The subjects studied were 13 students of group B. Data collection techniques are carried out through observation, interviews, and collecting documentation of each child as preliminary data for researchers. The results that have been collected are then analyzed in a descriptive quantitative manner. Based on the results that have been studied, it is revealed that in the teaching and learning process, the abilities of students can be assessed so that the results obtained, namely: 1) Flashcard game tools can improve cognitive skills in children, which can be seen from the achievement of all indicators of cognitive ability, namely there is an increase that occurs by two children obtaining Very Good Development (BSB) abilities, and there are ten children with the BSH category (Developing hope).